Stacking layer effect on mechanical and vibration behaviour of woven glass intertwined with kenaf fiber polymeric composites. (2022) - Ramraji, K.; Rajkumar, K.; Subbiah, M.; Balachandar, K.; Sarmaji Kumar, P.
Abstract: This research work will provide an investigation into the mechanical and vibration behaviour of glass intertwined with kenaf fiber laminates to help the modern automotive industry. Wet hand lay-up with compression loading was used to manufacture the glass interwoven kenaf polymer laminates. The mechanical properties of fabricated stacking composites, such as tensile and bending (flexural) strength, were investigated. The result revealed that the stacked glass intertwined kenaf fiber layer enhanced the tensile and flexural strength of the composites. In comparison to the other stacking composites, an alternate layer of glass and kenaf fiber with the glass skin layer of the interwoven epoxy composites (G4K3) had a higher tensile strength. Moreover, the natural fiber loading, outer layer, and inner core fiber effect of Kenaf intertwined glass fiber composite were studied. The free vibration properties like damping ratio and natural frequency of stacked kenaf epoxy composites were studied. The highest was the outside glass layer interlaced with five kenaf layered composites (G2K5), followed by the outer glass layers of alternative kenaf layered composites (G4K4) at both modes 1 and 2.